1990
DOI: 10.1002/1097-0142(19900915)66:6<1266::aid-cncr2820660628>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Cellular schwannoma. A clinicopathologic study of 57 patients and 58 tumors

Abstract: The cellular schwannoma is a variety of schwannoma with a predominantly cellular growth but no Verocay bodies. Because doubt has been raised about the original assessment of this tumor as benign, the clinical and pathologic characteristics of 58 cellular schwannomas from 57 patients were reviewed. The patients were most often middle aged (63% were female), and their tumors most commonly were painless masses with a predilection for the paravertebral region of the retroperitoneum, pelvis, and mediastinum. Most t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
135
0
9

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(148 citation statements)
references
References 25 publications
4
135
0
9
Order By: Relevance
“…It was first described in 1981 by Woodruff and co-workers (17), who stressed their benign clinical course and the importance of distinguishing them from malignant peripheral nerve sheath tumors. Subsequent studies have confirmed the benign nature of this tumor (18,19). As illustrated by the current cases, cellular schwannomas occur most often in the retroperitoneum and display histopathologic features that may result in their misdiagnosis as sarcoma or sarcomatoid carcinoma.…”
Section: Discussionsupporting
confidence: 59%
“…It was first described in 1981 by Woodruff and co-workers (17), who stressed their benign clinical course and the importance of distinguishing them from malignant peripheral nerve sheath tumors. Subsequent studies have confirmed the benign nature of this tumor (18,19). As illustrated by the current cases, cellular schwannomas occur most often in the retroperitoneum and display histopathologic features that may result in their misdiagnosis as sarcoma or sarcomatoid carcinoma.…”
Section: Discussionsupporting
confidence: 59%
“…They have an eosinophilic cytoplasm and elongated, wavy nuclei often hipercromatic and slightly pleomorphic. Verocay bodies are not present within the cellular schwannoma 11 . Also of note, aggregated of foamy histiocytes (lipid laden histio-cytes), hyalinized and thick-walled blood vessels and rare mitotic figures were also seen.…”
Section: Discussionmentioning
confidence: 87%
“…15,26 Whereas conventional schwannomas are more commonly seen in patients with NF2, 4% of cases of the cellular schwannoma variant, as seen in Case 1, occur in patients with NF1. 55 Patients with NF1 are also at risk for the development of MPNST, a high-grade soft-tissue sarcoma that can be quite difficult to cure. Patients with NF1 carry a 10% risk of development of an MPNST over their lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells display predominantly compact, Antoni A-like architecture, and Verocay bodies are rarely seen. 10,[53][54][55] Tumor cells show nuclear pleomorphism and hyperchromasia, often prompting an erroneous diagnosis of malignancy. 51,52,66 Recurrence has been documented in more than 20% of cases of cellular schwannoma in the peripheral nervous system, but data regarding CNS recurrence are lacking.…”
Section: Discussionmentioning
confidence: 99%